CONSTRUCTION OF LEGAL EDUCATION IN COLLEGE EDUCATION THROUGH PANCASILA EDUCATION - Nufikha Ulfah; Endrik Safudin; Yayuk Hidayah (Lambung Mangkurat Law Journal, 2021)
Legal awareness is a noble ideal when juxtaposed with the realization of smart and good citizens in Indonesia. This study aims to interpret, systematically identify efforts to build legal awareness in Higher Education. The research method used in this research is the Mixed Method. The data were obtained from a questionnaire given to 116 students from the non-law department and non-PPKn department at Ahmad Dahlan University, Yogyakarta. The results showed that 1) Building legal awareness through the substance of Pancasila Education material, 2) Student opinion about building legal awareness and law-abiding behavior was that 79% said it was enough, 12% was not optimal. 3) The relevance of Pancasila Education material with efforts to build legal awareness is Pancasila as an ethical system, Pancasila as a philosophical system, the practice of Pancasila, Pancasila as the state ideology, 4) Assessment in Pancasila education is through tests, observations, assignments and projects.